Implementing Character Education as Teachers’ Teaching Strategies - Mustasyfa Thabib Kariadi; Hotmauli Kumalasari; Muhamad Ahsanu (Dialektika Jurnal Pendidikan, 2025)
Character education remains a central concern in the field of education, aligning with Indonesia's national education goals that emphasize the importance of nurturing students' moral and ethical values. Teachers, as primary agents of classroom interaction, play a critical role in embedding character development within the learning process. This study investigates the pedagogical strategies employed by a teacher at SMP Al Irsyad Al Islamiyyah Purwokerto to integrate character education into daily instruction. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using thematic analysis. The findings reveal that the teacher implemented a diverse set of instructional strategies, including habituation, discovery learning, cooperative learning, blended learning, group discussions, interviews, and literacy-based activities. The novelty of this research lies in its contextualized analysis of character education strategies within an Islamic private junior high school setting, offering empirical insights into how varied pedagogical approaches are practically enacted in real classroom environments. The study contributes to the broader discourse on character education by providing a grounded framework for integrating moral development into subject teaching, particularly relevant for educators and policymakers aiming to reinforce values-based education in Indonesian schools.  Keywords: character education, teaching strategy